Axially‐confined in vivo single‐cell labeling by primed conversion using blue and red lasers with conventional confocal microscopes. (13th December 2017) - Taniguchi, Atsushi; Kimura, Yukiko; Mori, Ikue; Nonaka, Shigenori; Higashijima, Shin‐ichi
Abstract : Green‐to‐red photoconvertible fluorescent proteins have been found to undergo efficient photoconversion by a new method termed primed conversion that uses dual wave‐length illumination with blue and red/near‐infrared light. By modifying a confocal laser‐scanning microscope (CLSM) such that two laser beams only meet at the focal plane, confined photoconversion at the axial dimension has been achieved. The necessity of this custom modification to the CLSM, however, has precluded the wide‐spread use of this method. Here, we investigated whether spatially‐restricted primed conversion could be achieved with CLSM without any hardware modification. We found that the primed conversion of Dendra2 using a conventional CLSM with two visible lasers (473 nm and 635 nm) and a high NA objective lens (NA, 1.30) resulted in dramatic restriction of photoconversion volume: half‐width half‐maximum for the axial dimension was below 5 μm, which is comparable to the outcome of the original method that used the microscope modification. As a proof of this method's effectiveness, we used this technique in living zebrafish embryos and succeeded in revealing the complex anatomy of individual neurons packed between neighboring cells. Because unmodified CLSMs are widely available, this method can be widely applicable for labeling cells with single‐cell resolution. Abstract : The previous method (A) and the current method (B) of primed conversion. Spatially‐confined primed conversion can be achieved with this simple method.